2019
DOI: 10.1177/1756286419873518
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam and brivaracetam: a review of evidence from clinical trials and clinical experience

Abstract: Until the early 1990s, a limited number of antiepileptic drugs (AEDs) were available. Since then, a large variety of new AEDs have been developed and introduced, several of them offering new modes of action. One of these new AED families is described and reviewed in this article. Levetiracetam (LEV) and brivaracetam (BRV) are pyrrolidone derivate compounds binding at the presynaptic SV2A receptor site and are thus representative of AEDs with a unique mode of action. LEV was extensively investigated in randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 145 publications
2
34
0
Order By: Relevance
“…The pharmacokinetics of LEV is linear, with rapid and almost complete absorption and distribution into the cerebrospinal fluid compartment (Table 1). LEV is neither bound to plasma proteins nor metabolized in the liver by the CYP450 system [20]. There is one inactive metabolite LO57 which is formed by hydrolysis of the acetamide group [46].…”
Section: Piracetam and Its Newer Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…The pharmacokinetics of LEV is linear, with rapid and almost complete absorption and distribution into the cerebrospinal fluid compartment (Table 1). LEV is neither bound to plasma proteins nor metabolized in the liver by the CYP450 system [20]. There is one inactive metabolite LO57 which is formed by hydrolysis of the acetamide group [46].…”
Section: Piracetam and Its Newer Derivativesmentioning
confidence: 99%
“…BRV exhibits low protein binding and extensive metabolism [20,21]. A recent review suggested that the drug did not cause any clinically significant interactions by impairing drug-metabolizing CYP enzymes or drug transporters [156].…”
Section: Piracetam and Its Newer Derivativesmentioning
confidence: 99%
“…BRV was rationally developed based on the discovery of SV2A as the principal target of levetiracetam (Rogawski, 2008;Kaminsky et al, 2012, Klitgaard et al, 2016. Compared to levetiracetam, BRV has an order of magnitude higher affinity for SV2A, a distinct mode of interaction with SV2A, greater potency in common seizure models, and efficacy in a wider range of models (Klitgaard et al, 2016;Wood and Gillard, 2017;Wood et al, 2018;Steinhoff and Staack, 2019). The rpFPI-PTE model is based on a widely accepted clinically relevant traumatic brain injury model (Thompson et al, 2005;Lyeth, 2016) and likely incorporates epileptogenic mechanisms that operate after human head injury.…”
Section: Introductionmentioning
confidence: 99%
“…Brivaracetam (BRV; Brivact ® , Brivlera ® , UCB34714, C 11 H 20 N 2 O 2 ), a chemical analog of levetiracetam (LEV), is an orally or intravenously bioavailable racetam derivative with anticonvulsant (antiepileptic) properties that has appeared in a growing number of research papers [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Of note, it has also been recognized to be efficacious in the treatment of epilepsy and status epilepticus [ 9 , 17 , 30 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%